A Glyphosate-Based Herbicide in Soil Differentially Affects Hormonal Homeostasis and Performance of Non-target Crop Plants - Fuchs, Benjamin; Laihonen, Miika; Muola, Anne; Saikkonen, Kari; Dobrev, Petre I.; Vankova, Radomira; Helander, Marjo (Frontiers in Plant Science, 2022)
Glyphosate is the most widely used herbicide with a yearly increase in global application. Recent studies report glyphosate residues from diverse habitats globally where the effect on non-target plants are still to be explored. Glyphosate disrupts the shikimate pathway which is the basis for several plant metabolites. The central role of phytohormones in regulating plant growth and responses to abiotic and biotic environment has been ignored in studies examining the effects of glyphosate residues on plant performance and trophic interactions. We studied interactive effects of glyphosate-based herbicide (GBH) residues and phosphate fertilizer in soil on the content of main phytohormones, their precursors and metabolites, as well as on plant performance and herbivore damage, in three plant species, oat (Avena sativa), potato (Solanum tuberosum) and strawberry (Fragaria x ananassa). Plant hormonal responses to GBH residues were highly species-specific. Potato responded to GBH soil treatment with an increase in stress-related phytohormones abscisic acid, indole-3-acetic acid and jasmonic acid but a decrease in cytokinin ribosides and cytokinin-O-glycosides. GBH residues in combination with phosphate in soil increased aboveground biomass of potato plants and the concentration of the auxin phenylacetic acid but decreased phaseic acid and cytokinin ribosides and O-glycosides. Chorsimate-derived compounds (indole-3-acetic acid, phenylacetic acid and benzoic acid) as well as herbivore damage decreased in oat, when growing in GBH-treated soil but concentrations of the cytokinin dihydrozeatin and cytokinin ribosides increased. In strawberry plants, phosphate treatment was associated with an elevation of auxin (indole-3-acetic acid) and the cytokinin trans-zeatin, while decreasing concentrations of the auxin phenylacetic acid and cytokinin dihydrozeatin was observed in the case of GBH treatment. Our results demonstrate that ubiquitous herbicide residues have multifaceted consequences by modulating the hormonal equilibrium of plants, which can have cascading effects on trophic interactions.